Implementasi Peraturan Menteri Pendayagunaan Aparatur Negara dan Reformasi Birokrasi Republik Indonesia Nomor 17 Tahun 2021 Tentang Penyetaraan Jabatan Administrasi Ke Dalam Jabatan Fungsional di Kabupaten Trenggalek - Krisna Martha Ramadhan; Imam Fachruddin; Teguh Pramono; Daimul Abror; Muhamad Chairul Basrun Umanailo (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2023)
Simplification of the Bureaucracy into 2 (two) echelon levels, and replacing the positions of Administrator (echelon III) and supervisor (echelon IV) with functional positions (JF) that respect expertise and competence so that the bureaucracy is more effective and efficient in overcoming ASN issues that often get the spotlight on performance that looks bad or is still less than what the community expects. To describe and analyze as well as to find out what are the supporting and inhibiting factors How to implement the Regulation of the Minister of Empowerment of State Apparatus and Bureaucratic Reform of the Republic of Indonesia Number 17 of 2021 concerning Equalization of Administrative Positions into Functional Positions in Trenggalek Regency. Qualitative methods and policy implementation of George C Edward III's model. Based on 4 variables that determine the success of implementing a policy, namely Communication, Resources, Disposition, and Bureaucratic Structure, it is still not going well. In order to be able to carry out socialization, training, and technical guidance, then increase the number of competent policy implementers in accordance with functional position education.